Evaluation of activated irrigation techniques for the removal of calcium hydroxide from simulated internal root resorption cavities: an in vitro comparative study - Amira Shafie Ibrahim Mohamed; Dalia Mohamed Mukhtar Fayyad; Dalia Abd-Allah Mohamed (BMC Oral Health, 2026)
Abstract Background This study aimed to compare the calcium hydroxide [Ca(OH)₂] removal efficiency of six irrigation‑activation techniques and conventional syringe irrigation (control) from simulated internal root‑resorptive cavities in vitro. Materials and methods Seventy single-rooted human teeth were standardized to a length of 18 mm, prepared, and split longitudinally. A standardized hemispherical resorptive cavity was created in each root half; the halves were then reassembled and filled with premixed Ca(OH)₂. Specimens were incubated for 7 days and randomly allocated ( n = 10) to seven groups: (1) conventional syringe irrigation (control), (2) manual dynamic agitation (MDA), (3) XP‑Endo Finisher, (4) sonic EDDY, (5) sonic EQ‑S, (6) ultrasonic Irrisafe, or (7) ultrasonic Ultra X. In each irrigation protocol, two 30 s activations with 10 mL 2.5% NaOCl were used followed by one 30 s activation with 5 mL 17% EDTA. Residual Ca(OH)₂ percentages (%) within the simulated resorptive cavity (primary outcome) and the entire root canal system, including the coronal, middle, and apical thirds (secondary outcomes) was quantified stereo-microscopically using ImageJ software. Data were analyzed using Kruskal-Wallis and Friedman tests with Dunn–Bonferroni post hoc comparisons (α = 0.05). Results Significant differences were observed among the tested groups ( P ≤ 0.001). Within the simulated resorptive cavities, EDDY group demonstrated the significantly lowest percentage values of residual Ca(OH)₂ [median: 1.48%, IQR (0.65–1.59)] ( P < 0.05) followed by XP-endo Finisher [median: 23.31%, IQR (16.61–24.83)] and Irrisafe [median: 36.34%, IQR (14.31–49.05)] groups. EDDY, XP-Endo Finisher and Irrisafe groups showed the significantly lowest overall (total) percentage values ( P < 0.05), with no significant differences among them. Most irrigation protocols tested showed significant lower percentage values in the coronal third compared with the apical third, while no significant difference was detected between root thirds within the EDDY and Ultra X groups ( P = 0.199, P = 0.182). None of the tested techniques achieved complete removal of Ca(OH)₂. Conclusions Activated irrigation significantly enhances Ca(OH)₂ retrieval from internal resorptive defects; however, complete removal is not achieved with any of the tested techniques. EDDY demonstrates superior efficacy in removing Ca(OH)₂ specifically from simulated internal root resorption cavities. Across the entire root canal system, EDDY, XP-Endo Finisher, and Irrisafe demonstrate the highest overall efficacy for Ca(OH)₂ removal.